Recognition mechanisms of hemoglobin particles by monocytes – CD163 may just be one - Nimz, Jonathan-Gabriel; Rerkshanandana, Pichayut; Kloypan, Chiraphat; Kalus, Ulrich; Chaiwaree, Saranya; Pruß, Axel; Georgieva, Radostina; Xiong, Yu; Bäumler, Hans (Beilstein Journal of Nanotechnology, 2023)
Hemoglobin-based oxygen carriers (HBOCs) as blood substitutes are one of the great hopes of modern transfusion and emergency medicine. After the major safety-relevant challenges of the last decades seem to be largely overcome, current developments have in common that they are affected by degradation and excretion at an early stage in test organisms. Several possible mechanisms that may be responsible for this are discussed in the literature. One of them is CD163, the receptor of the complex of haptoglobin (Hp) and hemoglobin (Hb). The receptor has been shown in various studies to have a direct affinity for Hb in the absence of Hp. Thus, it seems reasonable that CD163 could possibly also bind Hb within HBOCs and cause phagocytosis of the particles. In this work we investigated the role of CD163 in the uptake of our hemoglobin sub-micron particles (HbMPs) in monocytes and additionally screened for alternative ways of particle recognition by monocytes. In our experiments, blockade of CD163 by specific monoclonal antibodies proved to partly inhibit HbMP uptake by monocytes. It appears, however, that several other phagocytosis pathways for HbMPs might exist, independent of CD163 and also Hb.
Keywords: CD163; HBOC; hemoglobin-based oxygen carriers; monocytes; phagocytosis